2015
DOI: 10.1080/00048623.2015.1024303
|View full text |Cite
|
Sign up to set email alerts
|

Linking Everyday Information Behaviour and Asian Immigrant Settlement Processes: Towards a Conceptual Framework

Abstract: International migration is a worldwide phenomenon. However, the process of immigrants' settlement is still considered an under-researched area from an information perspective. Navigating information throughout the settlement process is considered challenging but critical for immigrants. The uptake of information is deemed significant to both the well-being of immigrants and their host countries. An important outcome of the capability to navigate information in a new landscape is increasing the likelihood of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 29 publications
(51 reference statements)
0
57
0
1
Order By: Relevance
“…Notwithstanding the differences in terminologies and definitions of various types of international workers, and differences in newcomers' countries of origin, there is an important commonality in that newcomers need to find employment (with the exception of traditional expatriates who typically have jobs prior to migrating) to fully function and integrate in the country of destination (Cerdin et al, 2014;Crowley-Henry et al, 2016;Dietz et al, 2015;Fang et al, 2013;Frank, 2013;Guo and Al Ariss, 2015;Reitz, 2007a, 200b;Reitz et al, 2014). Integration of newcomers in the local labour market is critical for their successful settlement and adjustment, and overall wellbeing (Dietz et al, 2015;Hansen, 2012;Khoir et al, 2015b;Mahajan and Toh, 2014;Paul and Moser, 2009;Reitz et al, 2014;Wang and Sangalang, 2005).…”
Section: Labour Market Integration Of Newcomersmentioning
confidence: 99%
See 4 more Smart Citations
“…Notwithstanding the differences in terminologies and definitions of various types of international workers, and differences in newcomers' countries of origin, there is an important commonality in that newcomers need to find employment (with the exception of traditional expatriates who typically have jobs prior to migrating) to fully function and integrate in the country of destination (Cerdin et al, 2014;Crowley-Henry et al, 2016;Dietz et al, 2015;Fang et al, 2013;Frank, 2013;Guo and Al Ariss, 2015;Reitz, 2007a, 200b;Reitz et al, 2014). Integration of newcomers in the local labour market is critical for their successful settlement and adjustment, and overall wellbeing (Dietz et al, 2015;Hansen, 2012;Khoir et al, 2015b;Mahajan and Toh, 2014;Paul and Moser, 2009;Reitz et al, 2014;Wang and Sangalang, 2005).…”
Section: Labour Market Integration Of Newcomersmentioning
confidence: 99%
“…Limited or lack of local language proficiency is also a substantial barrier for newcomers seeking employment in the local market (Al Ariss and Syed, 2011;Fang et al, 2013;Syed, 2008;Syed and Murray, 2009;Turchick Hakak and Al Ariss, 2013). Lack of local language proficiency limits newcomers' employment opportunities, for example, by impacting the quality of their job applications (e.g., cover letters, resumes, and interview process) and by limiting their access to local information sources (Fang et al, 2013, Khoir et al, 2015bSirikul and Dorner, 2016). Research on newcomers in English-speaking countries showed substantial income differences between newcomers from English speaking and non-English speaking backgrounds (Syed, 2008;Syed and Murray, 2009).…”
Section: Lack Of Local Language Proficiencymentioning
confidence: 99%
See 3 more Smart Citations